Perencanaan Karir dalam Pendidikan Islam (Studi Literatur) - Aprima, Septi Gia; Jamilus, Jamilus (Indo-MathEdu Intellectuals Journal, 2024)
Islamic education. The research approach used is qualitative with a literature study method. The main source of research data is research articles published through various journals and indexed by google scholar. Data collection was carried out using the keyword "career in Islamic education". Articles used as primary data sources are articles published in the last 10 years. The data analysis used is qualitative data analysis consisting of data reduction, data presentation, and conclusion drawing. The findings of this study are that career planning in Islamic education begins with a deep understanding of oneself. Individuals are encouraged to understand their potential, interests, talents, and values, in line with Islamic teachings that emphasize the importance of introspection and self-discovery. With a deep understanding of themselves, individuals can identify career goals that align with religious values and qualified personal aspirations.